The Effect of Perceived Service Quality and Corporate Social Responsibility against Consumer Loyalty - Aldino, Aldino; Hanafiah, Ali (Journal of Sustainable Economic and Business, 2025)
Objectives: JNE is one of the dominant shipping service companies in Mataram, West Nusa Tenggara, facing challenges due to a decline in sales targets. Therefore, the research aims to determine how impact Perceived Service Quality, Corporate Social Responsibility (CSR), and Customer Satisfaction with Customer Loyalty to JNE in Mataram, West Nusa Tenggara. Methodology: The research design used in this study is quantitative research, with data collection method using survey method. and research instrument in the form of questionnaires share with respondents online is designed with specific criteria and weighted values based on a Likert scale. The research method employed is causal analysis. The sample consists of 133 respondents selected through purposive sampling. The data analysis model used is Partial Least Squares (PLS), and analysis technique applied is descriptive. Finding: The research findings indicate that Perceived Service Quality, CSR, and Customer Satisfaction had a positive and significant influence on Customer Loyalty. Conclusion: The indirect effect analysis reveals that Customer Satisfaction acts as a mediator in the relationship between Perceived Service Quality and Customer Loyalty, as well as between CSR and Customer Loyalty.